2006
DOI: 10.1001/archpsyc.63.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Increased Hippocampal Plaques and Tangles in Patients With Alzheimer Disease With a Lifetime History of Major Depression

Abstract: In AD, the presence of a lifetime history of depression corresponds to increases in AD-related neuropathological changes within the hippocampus. These changes go along with more rapid cognitive decline in patients with AD with a history of depression, and are more pronounced in patients with AD suffering from depression early on in the disease process, suggesting an interaction between major depression and AD neuropathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
221
3
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(250 citation statements)
references
References 50 publications
14
221
3
6
Order By: Relevance
“…A separate prospective study, which conducted a neuropathological evaluation of the post-mortem brains of patients with a mean age of 81 years, found the presence of a higher number of neuritic plaques and neurofibrillary tangle formations in the hippocampus of patients with AD with a history of depression, as compared with brains of AD patients without depression history (Rapp et al 2006).…”
Section: Bipolar Disorder and Depressionmentioning
confidence: 99%
“…A separate prospective study, which conducted a neuropathological evaluation of the post-mortem brains of patients with a mean age of 81 years, found the presence of a higher number of neuritic plaques and neurofibrillary tangle formations in the hippocampus of patients with AD with a history of depression, as compared with brains of AD patients without depression history (Rapp et al 2006).…”
Section: Bipolar Disorder and Depressionmentioning
confidence: 99%
“…There is evidence that hippocampal atrophy, in addition to being a classic feature of many dementias and aging itself, confers vulnerability to depression. 47-48 Some of the processes with presumed etiological roles could be subsumed under the vascular or inflammatory hypotheses, but others such as amyloid plaque formation 49-50 are unique to this hypothesis. Interestingly, hippocampal regions have been found to be especially vulnerable to ischemia 51 and to activation of the hypothalamic-pituitary-adrenal (HPA) axis, resulting from stress and chronic medical illness.…”
Section: Current Hypotheses For Biological Mechanisms Promoting Lldmentioning
confidence: 99%
“…Three patients with AD pathology also displayed evidence of vascular disease and the other three demonstrated Lewy body pathology (dementia with Lewy bodies being the secondary diagnosis). In another recent neuropathological study, increased numbers of plaques and tangles in the hippocampal region were identified in post mortem tissue in AD patients with prior episodes of major depression (Rapp et al, 2006). The density of plaques and tangles were even greater in patients in whom there was concurrent depression and dementia at the time of the initial AD diagnosis (Rapp et al, 2006).…”
Section: The Role Of Amyloid and Taumentioning
confidence: 96%
“…MDD has been identified both as a risk factor and a prodrome of Alzheimer's disease (AD) in clinical and community samples (Reding et al, 1985;Kral and Emery, 1989;Kokmen et al, 1991;Jorm et al, 1991;Alexopoulos et al, 1993b;Speck et al, 1995;Devanand et al, 1996;Henderson et al, 1997;Steffens et al, 1997;Bassuk et al, 1998;Chen et al, 1999;Yaffe et al, 1999;Geerlings et al, 2000;Jorm, 2000;Lockwood et al, 2000;Visser et al, 2000;Jorm, 2001;Lockwood et al, 2002;Wilson et al, 2002;Green et al, 2003;Sweet et al, 2004;Cannon-Spoor et al, 2005;Gatz et al, 2006;Rapp et al, 2006;Steffens et al, 2006). Community based studies have identified clinical depression, including depressive symptoms as a risk factor for the subsequent development of dementia.…”
Section: Relationship Of Mdd To Admentioning
confidence: 99%